A history of global Anglicanism - Ward, Kevin, 1947- (Cambridge, UK ; New York : Cambridge University Press, 2006)
Anglicanism can be seen as irredeemably English. In this book Kevin Ward questions that assumption. He explores the character of the African, Asian, Oceanic, Caribbean and Latin American churches which are now a majority in the world-wide communion, and shows how they are decisively shaping what it means to be Anglican. While emphasising the importance of colonialism and neo-colonialism for explaining the globalisation of Anglicanism, Ward does not focus predominantly on the Churches of Britain and N. America; nor does he privilege the idea of Anglicanism as an 'expansion of English Christianity'. At a time when Anglicanism faces the danger of dissolution Ward explores the historically deep roots of non-Western forms of Anglicanism, and the importance of the diversity and flexibility which has so far enabled Anglicanism to develop cohesive yet multiform identities around the world.
Introduction: 'Not English, but Anglican' -- The Atlantic Isles and world Anglicanism -- The United States -- Canada -- The Caribbean -- Latin America -- West Africa -- Southern Africa -- East Africa -- The Middle East -- South Asia -- China -- The Asian Pacific -- Oceania -- The Anglican communion : escaping the Anglo-Saxon captivity of the church?
Includes bibliographical references (pages 336-355) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Anglican Communion -- History; RELIGION -- Christianity -- Anglican; Anglican Communion; Electronic books; History